Injury epidemiology in professional ballet: a five-season prospective study of 1596 medical attention injuries and 543 time-loss injuries - Mattiussi, A. M.; Shaw, J. W.; Williams, S.; Price, P. D.; Brown, D. D.; Cohen, D. D.; Clark, R.; Kelly, S.; Retter, G.; Pedlar, C.; Tallent, J. (British Journal of Sports Medicine, 2021)
OBJECTIVES: To describe the incidence rate, severity, burden and aetiology of medical attention and time-loss injuries across five consecutive seasons at a professional ballet company.